Protection of forest lands in the Russian Federation: Problems and solutions - Serebryakov Oleg; Yakovenko Natalia; Komov Igor; Kolotushkin Andrey (BIO Web of Conferences)
The article deals with topical issues of forest land protection in the Russian Federation in the context of modern environmental and legal challenges. The main attention is paid to the analysis of the current forest legislation, its shortcomings and potential for improvement in order to increase the effectiveness of protection measures. Data on the current state of forest resources are presented, including statistics on degradation and restoration of forest ecosystems. The article also explores economic and social aspects of forest management, with special attention paid to the role of local communities and the importance of their participation in the processes of forest land protection and restoration forest lands Based on international experience, specific recommendations are offered to strengthen the legal protection of forests and introduce innovative approaches to monitoring and management of forest resources. The significance of the study lies in practical recommendations to improve the efficiency of rational and sustainable use of forest land in the Russian Federation, as well as proposals to improve the mechanisms of protection and conservation of Russian forests. The work is designed to promote a constructive dialogue between government agencies, the scientific community and non-governmental organizations aimed at achieving sustainable management of Russia’s forest fund.